Persepsi Dukungan Organisasi Memoderasi Variabel Sikap dan Persepsi Kontrol Perilaku Terhadap Niat Whistleblowing - Novita Sari; Fachruzzaman Fachruzzaman; Darman Usman; Indah Oktari (Jurnal Akuntansi dan Keuangan Daerah, 2023)
Whistleblowing is an act of reporting fraud or violations committed by internal or external parties within an organization, Whistleblowing has an important role in uncovering fraud. This study aims to examine employee attitudes and perceptions of behavior control that affect whistleblowing intentions and perceptions of organizational support can be a moderating variable for attitudes and perceptions of behavior control. The sample in this study were employees of the Bengkulu City Tax Office. The data used in this research is primary data. The data collection method used a purposive sampling technique and this research used quantitative. Data were analyzed using multiple linear regression using SPSS 25 software. The results of testing the hypothesis in this study show that employee attitudes have a positive effect on whistleblowing intentions, perceived behavioral control has no effect on whistleblowing intentions, perceived organizational support cannot be a variable that moderates employee attitudes towards whistleblowing intentions, perceived organizational support can be a moderating variable that strengthens the effect of perceived behavioral control on whistleblowing intentions. In future research, it is hoped that the scope of research will be further expanded, not only at the Bengkulu City KPP, but can add to other organizations that are also prone to commit acts of fraud. It is also hoped to add other factors that can affect whistleblowing intentions, this is because there are still 70% more factors that influence whistleblowing intentions beyond the factors examined in this study.